Analisis Pengaruh Penerapan Sistem Manajemen Mutu ISO 9001:2000 terhadap Kinerja Karyawan (Studi Kasus PT. Brantas Abipraya Wilayah I Medan) - Sutoyo, Sutoyo (JURNAL VARIASI, 2011)
The application of quality management system in a construction service company is a need to help the company is able to compete and to continuously improve its performance in line with technology development and changes of circumstance. Quality management system of ISO 9001:2000 is an international standard aimed at providing quality guarantee through documented requirements to meet customerâsÂ  satisfaction.The problem of this research is how the application ofÂ  ISO 9001:2000 based quality management system including competency, awareness and training, infrastructure and work environment influences the workÂ  performance of theÂ  employees of PT. Brantas Abipraya RegionalÂ  I Medan. This research is intended to examine the influence of the application of ISO 9001:2000 based quality management system including competency, awareness and training, infrastructure and work environment on the work performance of the employees of PT. Brantas AbiprayaÂ  RegionalÂ  I Medan. This research use the theories of production management and humanÂ  resources management related to theÂ  ISO 9001:2000 based quality management system including competency, awareness and training, infrastructure and work environment. The descriptive explanatory research usesÂ  survey method in the form of case study and the data obtained were analyzed through multiple linear regression method. The result of this researchÂ  shows that there is a simultaneous significant influence beween competency, awareness and training (X1), infrastructure (X2), work environment (X3), upon the employeeâs performance (Y), at PT. BrantasÂ  Abipraya RegionalÂ  I Medan, atÂ  the level ofÂ  confidence of 95. Partially each variable with the level of confidence of 95%Â  (significanceÂ  Î± = 0.05), has a significant influence on teh employeeâs performance